지속가능개발목표(SDGs)에 기반한 ‘세계시민교육과 리더십’ 교양교과목의 사례 연구 - 김경아(Kim, Kyoung-A) (교양교육연구, 2018)
본 연구의 목적은 개인의 성장과 세계시민으로서의 역량함양을 위해 개설된 교과목의 효과성 을 검증함으로써, 향후 글로벌 리더 양성을 위한 가능성과 방향을 탐색해 보고자 한다. 연구대상 은 S여자대학교 교양필수 교과목으로 운영되고 있는 ‘세계시민교육과 리더십’ 강좌이다. 보다 면 밀하고 심층적인 자료를 얻기 위해 2017년 1, 2학기에 본 교과목을 수강한 학생 총 16명을 4회 차로 나누어 FGI를 실시하였다. 1학년 신입생이며 전공은 다양하게 표집하였다. 연구참여자의 윤 리적 측면을 고려한 제반 절차를 거쳤으며 모든 자료는 전사 과정을 거쳐 범주화되었다. 연구결과 교과목의 의의와 운영시스템, 자신과 타인에 대한 긍정적 이해의 확장, 글로벌 시티 즌십 고취 등의 총 3개 범주에 대해 8개 하위범주, 31개 개념이 도출되었다. 즉 수강생들은 본 교 과목을 통해 학교에 대한 애착과 소속감이 증진되었으며, 교수자의 피드백이나 평가 시스템 등 교과목 운영에 대해서도 긍정적으로 평가하는 것으로 나타났다. 다음 본 수업을 수강하면서 자 신의 과거와 미래에 대한 진지한 성찰의 계기가 되었음을 알 수 있다. 끝으로, 세계 이슈에 대한 인식 개선과 정보 습득 및 세계시민의 한 사람으로서의 행동 변화를 일으키는 동기부여를 제공 했음을 확인하였다. 이와 같이 본 교과목은 신입생 시기 성숙한 인간으로서의 패러다임 전환과 세계시민으로서의 사명감을 고취시키는데 기여했음을 알 수 있다. The purpose of this study is to investigate the effectiveness of a course subject, created to promote personal growth as well as the traits required of a global citizen, was subjected to verification. In turn, this investigation would lead to a discussion on the implications and possibilities of cultivating future global leaders. The subjects of this study were participants of ‘Global Citizen Education and Leadership’, a mandatory liberal arts course in S Women’s University. To extract data of detail and depth, the study implemented four series of focus group interview(FGI) on a total of 16 students who took the course throughout the first and second semester of 2017. These students were in their freshmen year, sampled from a wide scope of majors. Necessary procedures were taken to prevent ethical breaches from study participants, and all data were categorized through a process of transcription. As a result of the study, a total of 8 subcategories with 31 concepts were derived from 3 areas of categories, including understanding of the course and its system, expanding the positive understanding of one’s self and others, and cultivating global citizenship. Conclusively, the participants of the course experienced an elevation of attachment and a sense of belonging to the school, providing a positive assessment of the lecturer and of the course management system. In addition, the participation of the course proved to have been a momentum for serious reflection on the students’ pasts and futures. Finally, it was verified that the course had improved awareness of global issues and of the means to attain information. Also, it provided sufficient motivation to change patterns of behavior to befit that of a global citizen. It can be concluded that the course subject proposed by this study provided a timely shift in paradigm for freshmen students to grow as mature human beings. Furthermore, it contributed to the incorporation of a sense of duty as global citizens, providing even more room for growth to students. KCI Citation Count: 4